Comparison of fire resistance of polymers in intumescent coatings for steel structures - Кalafat, Kostyantyn; Taran, Nadezhda; Plavan, Viktoriia; Bessarabov, Volodymyr; Zagoriy, Glib; Vakhitova, Liubov (Eastern-European Journal of Enterprise Technologies, 2020)
Thermal destruction of fire-retardant intumescent coating of the composition of ammonium polyphosphate (APP)/melamine (MA)/pentaerythrite (PE)/titanium oxide (TiO2)/polymer, which can be applied for fire protection of steel structures, was studied. The influence of polymers of different nature – ethylene-vinyl acetate (EVA), vinyl acetate versatate (VAVV), styrene acrylates, and vinyl toluene acrylate on the processes of formation of a coke layer and fire-retardant effectiveness of appropriate coatings was determined. Chemical transformations of polymers EVA and styrene acrylate in the intumescent system of ARR/MA/PE/TiO2 in the temperature range of 200–800 °С were studied. It was established that the processes of the thermal destruction of vinyl acetate polymer are more harmonized with chemical reactions of the components of the intumescent system than similar processes for acrylate aromatic polymers. Thermal-oxidation destruction of intumescent compositions at the temperatures of 200–800 °С was explored. It was shown that basic chemical processes with polymers of EVA and VAVV begin after 300 °С and flow in the temperature range of 350–600 °С. It was found that the noticeable degradation of the carbon-phosphorus frame of intumescent compositions with styrene acrylate polymers begins at 450 °С, which is almost by 150 °С below the temperature of degradation of the compositions containing vinyl acetate binders. The conducted fire tests demonstrate that intumescent compositions with the use of acrylate aromatic polymers are more effective at the low coating thickness in ensuring the fire resistance boundary of 30 min. In order to ensure higher values of fire resistance, it is necessary to use intumescent coatings containing vinyl acetate co-polymers as the polymer component. The study of the impact of polymers of intumescent coatings on the boundary of fire resistance of steel structures has scientific and practical significance for the development of differentiated fire protection means, oriented to the given class of fire resistance. Fire-retardant intumescent compositions examined in this study can be used as the basis for the formulations of materials for fire protection of building structures under conditions of a standard fire